MODEL DESA TERPADU PAUDNI MEWUJUDKAN MASYARAKAT PEMBELAJAR SEPANJANG HAYAT - Sadid, Agus (JIV-Jurnal Ilmiah Visi, 2014)
The pattern of rural development should move towards an integral-concept of development. Early childhood education program, (PAUDNI) has a huge potential to enhance people’s welfare. The village model of PAUDNI would be the best alternative solution of empowering community. The problem is how to develop the integrated village model that establishes a life-long learning community. This article describes, discusses, and explores the integrated village model of PUDNI. The conclusion is (1) the PAUDNI village is constructed by the andragogy theory by Knowles and Pannen, emphasizing the community empowerment on integral and integrated aspects; (2) the construction of PAUDNI village model includes community participations, cooperation, commitment, and integrity; (3) the implementation of the model should consider data and analysis, community participation, PAUDNI Units such as PKBM, LKP, PAUD and other non-formal and informal groups; (4) in supervision and guidance process, the model of PAUNI village should involve some related people or institutions. Implementing such a village model properly would create a life-long learning community and enhance the social welfare and the life quality of the community.